Uptake capacity of metals (Al, Cu, Pb, Sn, Zn) by Vetiveria Zizanioides in contaminated water in the Dong Xam metal production trade village, Thai Binh, Vietnam - Minh*, Nguyen Trung; Taek Yun, Seong-; Soon Kwon, Jang-; Tra, Doan Thu; Hung, Doan Dinh (Vietnam Journal of Earth Sciences, 2016)
This study presents an experiment of metal contaminated water treatment under controlled environment conditions to investigate the uptake capacity of metals by Vetiveria Zizanioides to treat contaminated water from a metal production trade village, Dong Xam, Thai Binh, Vietnam. Vetiver was grown in two pot culture experiments TB10, TB6 with solutions containing respective concentrations of Al, Cu, Pb, Sn and Zn of 2.5, 55.6, 0.15, 7.7 and 24.4 mg from contaminated water in the Dong Xam metal production trade village for a period of 36 days. Vetiver has the higher tolerance to Al, Cu, Pb, Sn and Zn than other plant species. The roots (hereafter R) are high Al hyperaccumulators, concentrating 17 up to 30 folds more than “reference plant”. The upper parts of shoots (hereafter S1, S2, and S3) are 1.2 folds higher. Cu concentration in the root and shoot is up to 660 and 46.2 mg/kg, respectively. Vetiver can withstand and survive at Cu concentration of 46 mg/L in contaminated water that is markedly higher than other plants that can last only in solution with Cu concentration ranging 20-100 mg/kg. The translocation of Pb from root to shoot was 41%. Sn is more accumulated in the top, in which shoot/root ratio varied from 82% to 277% in the top, and increased to the top (by order S3/R>S2/R>S1/R). Zn could be translocated from roots and accumulated in shoots of vetiver. The ratio shoot/root obtains up to 46%. The present results demonstrated that vetiver had the high tolerance to trace metals Al, Cu, Pb, Sn and Zn in vegetation. This plant has a potential phytoremediation of metals in contaminated soil and wastewater from trade villages of Vietnam and other countries.References Adriano D.C., 1992. Biochemistry of trace metals. Lewis Publishers. Boca Raton, New York. 513 pp. Baker D.E., 1976. Acid soils. In Proc. of Workshop on Plant Adaptation to Mineral Stress in Problem Soils. Wright J. Ed. Cornell University. Ithaca. No4, 127. Becker H., 1992. Hedging against erosion. Agric. Res. 12, p.8-10. Braude G.L., Nash A.M., Wols W.J., 1980. Cadmium and lead content of soybean products. J. Food Sci., 45, 1187. Broyer T.C., Johnson C.N. and Paull R.E., 1972. Some aspects of lead in plant nutrition. Plant Soil. V36, p.301. Chiu K.K., Ye Z.H., Wong M.H., 2005. Enhanced uptake of As, Zn, and Cu by Vetiveria zizanioides and Zea mays using chelating agents. Chemosphere, 60, p.1365-1375. Chiu K.K., Ye Z.H., Wong M.H., 2006. Growth of Vetiveria zizanioides and Phragmities australis on Pb/Zn and Cu mine tailings amended with manure compost and sewage sludge: A greenhouse study. Bioresource Technology, 97, p.158-170. Cull, R.H., Hunter, H., Hunter, M., and Truong, P.N.,  2000.  Application of Vetiver Grass Technology in off-site pollution control.  II.  Tolerance of Vetiver grass towards high levels of herbicides under wetland conditions.  Proceedings of the Second International Vetiver Conference, Phetchaburi, Thailand, January 2000. Dabin P., Marafante E. et al., 1978. Adsorption, distribution and binding of cadmium and zinc in irrigated rice plants. Plant soil, 50, p. 329. Foy C.D., Chaney R.L. and White M.C., 1978. The physiology of metal toxicity in plants. Annu. Rev. Physiol. 29, p.511. Frank R., Stonefield K.I. and Suda P. 1979. Metals in agricultural soils of Ontario. Can. J. Soil Sci., 59, p.99. Grimshaw R G., 1989. A review of existing soil conservation technologies, and a proposed method of soil conservation using contour farming practices backed by vetiver grass hedge barriers. In Proc. vetiver Grass Seminar at the Int. Agric. Centre in Wageningen, The Netherlands, January, 1989. Hung-Yu Lai, Zueng-Sang Chen, 2004. Effects of EDTA on solubility of cadmium, zinc, and lead and their uptake by rainbow pink and vetiver grass. Chemosphere, 55, p.421- 430. Jensen K., Stephenson G., Hunt, L., 1977. Detoxification of atrazine in three Gramineae subfamilies. Weed Sci. 25, p.212-220. Kabata-Pendias Alina and Pendias Henryk, 2001. Trace elements in soils and plants. 3rd ed. CRC Press, Inc. Boca Raton, Florida, 413pp. Leckie J. O. and Davis J. A., 1979. Aqueous environmental chemistry of copper. In Copper in Environment (ed. J. O. Nriagu). Wiley, New York, pp.90-121. Markert B., 1992. Establishing of “reference plant” for inorganic characterization of different plant species by chemical fingerprinting. Water, Air, and Soil Pollution, 64: p.533-538. Mejare M., Bulow L., 2001. Metal-binding proteins and peptides in bioremediation and phytoremediation of heavy metals. Trends in Biotechnology, 19, p.67-73. Mickovski S.B., Beek L.P.H van and Salin F., 2005. Uprooting of vetiver uprooting resistance of vetiver grass (Vetiveria zizanioides). Plant and Soil, 278, p.33-41. Rommey E.M., Wallace A., and Alexander G.V., 1975. response of bush bean and barley to tin applied to soil and to solution culture. Plant Soil, 42, p.585. Sanita di Toppi L, Gabbrielli R. 1999. Response to cadmium in higher plants. Environ Exp Bot; 41:p.105-130. Schlesinger W. H. 2004. Treatise on geochemistry. Volume 8 Biogeochemistry. Executive editors H. D. Holland and K. K. Turekian. First edition 2004. Elsevier-Pergamon, Oxford. Steven T. S., Paul R. A., Ricarda N. K., 1999. Aquaculture sludge removal and stabilization within created wetlands. Aquacult. Eng. 19, p.81-92. Sylvie M., Muriel R., Patrick R., Jean-Paul S., 2006. Conjugation of atrazine in vetiver (Chrysopogon zizanioides Nash) grown in hydroponics. Environmental and Exp. Botany, 56, p.205-215. Tordoff G.M., Baker, A.J.M., Willis, A.J., 2000. Current approaches to the revegetation and reclamation of metalliferous mine wastes. Chemosphere, 41, p.219-228. Truong P. and Loch R., 2004. Vetiver System for erosion and sediment control. In Proc. 13th International Soil Conservation Organisation Conference, Brisbane, Australia, July 2004. pp.1-6. Truong P.N., 1996. Vetiver grass for land rehabilitation. In: Proceedings of the First International Vetiver Conferences, Thailand, pp.49-56. Truong P.N. and Baker D., 1998. Vetiver Grass System for Environmental Protection. Technical Bulletin N0. 1998/1.  Pacific Rim Vetiver Network, Office of the Royal Development Projects Board, Bangkok, Thailand. Truong P.N. and Hart B., 2001.  Vetiver System for Wastewater Treatment. Technical Bulletin NO. 2001/2.  Pacific Rim Vetiver Network, Office of the Royal Development Projects Board, Bangkok, Thailand. Veldkamp J. F., 1999. A revision of Chrysopogon Trin., including Vetiveria Bory (Poaceae) in Thailand and Malesia with notes on some other species from Africa and Australia. Austrobaileya 5: p.522-523. Wilde E.W., Brigmon R.L., Dunn D.L., Heitkamp M.A., Dagnan D.C., 2005. Phytoextraction of lead from firing range soil by Vetiver grass. Chemosphere, 61, p.1451-1457. World Bank, 1990. Vetiver Grass - The Hedge Against Erosion, 3rd ed. Washington D.C. Xia H.P., 2004. Ecological rehabilitation and phytoremediation with four grasses in oil shale mined land. Chemosphere, 54, p.345-353. Yahua C., Zhenguo S., Xiangdong L., 2004. The use of vetiver grass (Vetiveria zizanioides) in the phytoremediation of soils contaminated with heavy metals. Applied Geochemistry, 19, p.1553-1565. Yang B., Shu W.S., Ye Z.H., Lan C.Y., Wong M.H., 2003. Growth and metal accumulation in vetiver and two Sesbania species on lead/zinc mine tailings. Chemosphere, 52, p.1593-1600. Zhang J., 1998. Benefit and application future of sandy soils on windy Pingtan island. In: Vetiver Research and Development. Agricultural Science and Technology Press, China, pp.179-191. Zimdahl R.L., 1975. Entry and movement in vegetation of lead derived from air and soil sources. Paper presented at 68th Annu. Meeting of the Air Pollution Control Association, Boston, Mass., June 15, 1975, 2.